PERLINDUNGAN HUKUM KORBAN TINDAK PIDANA TERORISME: ANTARA DESIDERATA DAN REALITAï€ª - Hendriana, Rani (Kosmik Hukum, 2016)
The existence of legal protection for victims of criminal acts of terrorism is the greatest desiderata for the victims, however, is not the case with the existing reality. Things are interesting to study, regarding legal protection for victims of criminal acts of terrorism in Indonesian positive criminal law and the factors inhibiting the provision of legal protection. The method used is normative. The results indicate that there are three legislations were oriented towards victims of criminal acts of terrorism, however, in reality does not match the expectations of victims where there are still weaknesses, both in the aspect of legal substance component, legal structure, and legal culture. In response, the strengthening of legal substance, structure and culture needs to be done. Keywords: Protection, victims of terrorism, reality, desiderata